Powder magnetic core and manufacturing method thereof
Patent Information
- Application Number
- JP2020207357
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-15
- Publication Date
- 2025-02-19
- Estimated Expiration
- 2040-12-15
AI Technical Summary
【0014】 本開示の一実施形態によれば、低鉄損であり、寸法精度に優れる圧粉磁心を提供することができる。
Smart Images

Figure 0007631776000003 
Figure 0007631776000001 
Figure 0007631776000002
Abstract
Description
[Technical field]
[0001] An embodiment of the present invention relates to a powder magnetic core and a method for producing the same. [Background technology]
[0002] A dust core in which soft magnetic powder is bound with a binder such as resin has the advantage of being able to reduce material costs and has a higher material yield during manufacture than a laminated core made from silicon steel sheets, etc. It also has the advantage of being able to improve magnetic properties by optimizing the design of the core shape, with a high degree of freedom in shape. In such dust cores, the eddy current loss of the magnetic core can be significantly reduced by improving the electrical insulation between the metal powders by mixing the soft magnetic powder with an insulating material such as an organic binder or inorganic powder, or by coating the surface of the soft magnetic powder with an electrically insulating coating.
[0003] Due to these advantages, dust cores are used in transformers, reactors, thyristor valves, noise filters, choke coils, etc., and are also used in motor cores, rotors and yokes for motors for general home appliances and industrial equipment, and solenoid cores (stationary iron cores) for solenoid valves incorporated in electronically controlled fuel injection devices for diesel engines and gasoline engines, and are increasingly being applied to various soft magnetic parts. Dust cores can reduce eddy current loss in the high frequency range compared to silicon steel sheets, and the use of dust cores in high frequency applications such as reactors is increasing. In addition, the use of higher frequencies in the frequency band allows the magnetic core itself to be made smaller, and the number of coil windings and the amount of copper used can be reduced, resulting in space savings and cost reductions for electronic devices that use them. For this reason, in recent years, many electronic devices have become more and more frequent, and the development of high frequency compatible materials has progressed rapidly.
[0004] The molding methods for powder magnetic cores are roughly divided into injection molding, in which soft magnetic powder is injected together with plastic raw materials into a mold that defines the product shape, and compression molding, in which raw powder containing soft magnetic powder and a binder is filled into the cavity of a mold and compressed with upper and lower punches. The product shape of powder magnetic cores is given in the molding process, and the molding method used is determined according to the product application.
[0005] In response to the recent demand for smaller and lighter household and industrial devices, there is a growing demand for powder cores with improved magnetic properties such as magnetic flux density. Since the space factor of soft magnetic powder in a powder core is proportional to the magnetic flux density, there is a method for increasing density to obtain a powder core with high magnetic flux density. For this reason, the compression molding method, which can reduce the amount of binder and increase the amount of soft magnetic powder, and can mold at a high density, is widely used compared to the injection molding method, which requires a large amount of binder.
[0006] In a method of compression molding a powder magnetic core, when the powder compact is extruded from the cavity of a mold, the side surface of the powder compact is pressed against the inner peripheral surface of the mold while sliding against it, which may cause plastic flow at the sliding surface of the powder compact. At the sliding surface of the powder compact where plastic flow has occurred, the particles of the soft magnetic powder are deformed or destroyed, which may lead to a decrease in insulation due to conduction between the particles of the soft magnetic powder or exposure of the conductive parts inside the particles of the soft magnetic powder. Patent Document 1 proposes forming a lubricating coating on the inner peripheral surface of a mold cavity, which reduces the frictional resistance between the inner peripheral surface of the mold cavity and the sliding surface of the powder compact when the powder compact is extruded from the mold cavity, suppresses the occurrence of plastic flow at the sliding surface of the powder compact, and maintains the insulation state of the resulting powder core. A powder core that maintains its insulation state can suppress an increase in eddy current loss, and can be preferably used in high frequency applications.
[0007] Patent Document 2 proposes forming a high-resistance area on part of the sliding surface of the powder compact to make the pressure surface of the powder compact highly resistive in order to block eddy currents that flow in the circumferential direction about an axis perpendicular to the pressure surface of the powder compact and reduce eddy current loss. In Patent Document 2, the proportion of coarse iron-based particles is limited to prevent damage to the insulating coating of the iron-based particles when the powder compact is pressed by a punch member, thereby making the punch surface of the powder compact high resistance. Also, in Patent Document 2, when a conductive part is formed by the sliding contact surface of the powder compact and the molding die, causing the sliding contact surface to have low resistance, a high resistance region is formed by subjecting the conductive part to laser treatment, acid treatment, or the like. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 2015 / 046282 [Patent Document 2] JP 2013-131676 A Summary of the Invention [Problem to be solved by the invention]
[0009] In Patent Document 1, in order to maintain the insulation state of the powder magnetic core, a lubricating coating is brought into contact with the entire surface of the side of the powder compact inside the cavity of a molding die, thereby attempting to suppress the occurrence of plastic flow over the entire sliding surface of the resulting powder magnetic core. In Patent Document 2, when plastic flow occurs and the sliding surface becomes low resistance, a small area of the sliding surface is laser-treated to form a partially high-resistance area, but the area where insulation is reduced due to plastic flow occupies most of the sliding surface. In Patent Document 2, a powder compact in which plastic flow has occurred on the sliding surface is acid-treated to remove the entire conductive part of the surface, but the acid treatment causes changes in surface properties, dimensional errors, and process complication. In Patent Document 2, a lubricant is applied to the inner peripheral surface of a molding die and then pressure-molded to reduce frictional resistance with the sliding surface of the powder compact, thereby obtaining a powder compact with a sliding surface that is generally high resistance.
[0010] By bringing a lubricating coating into contact with the entire side surface of the green compact in the cavity of a mold during compression molding of a powder magnetic core, the occurrence of plastic flow is suppressed over the entire side surface of the obtained powder magnetic core, maintaining an insulating state, and providing a powder magnetic core with low iron loss. Meanwhile, dimensional accuracy is also important when compression molding a powder magnetic core to a high density, but the dimensional accuracy has not been sufficiently improved with the surface properties of the side surface of the above-mentioned powder magnetic core.
[0011] An object of the present disclosure is to provide a powder magnetic core that has low core loss and excellent dimensional accuracy. [Means for solving the problem]
[0012] One embodiment of the present disclosure relates to the following. [1] A powder magnetic core which is a green compact obtained by compression molding soft magnetic powder, wherein the sliding surface of the green compact has an area having a resistivity of 5 Ω·cm or more of 20% to 80% by area of the entire sliding surface, and an area having a resistivity of 1 Ω·cm or less of 20% to 80% by area of the entire sliding surface. [2] The powder magnetic core according to [1], wherein the region having a resistivity of 5 Ω·cm or more accounts for 40 area % or more of the entire sliding contact surface. [3] The powder magnetic core according to [1], wherein the region having a resistivity of 5 Ω cm or more has a surface layer portion having a structure in which insulating particles are present between particles of soft magnetic powder. [4] The powder magnetic core according to [1], wherein the region having a resistivity of 5 Ω cm or more has an area ratio of insulating particles of 30% or more in a component map obtained by electron probe microanalysis. [5] The powder magnetic core according to [3] or [4], wherein the insulating particles include at least one type selected from the group consisting of molybdenum disulfide particles and insulating ceramic particles. [6] The powder magnetic core according to any one of [1] to [5], wherein the soft magnetic powder has an insulating coating covering the surface.
[0013] [7] A method for manufacturing a green compact for a magnetic core, comprising: forming an insulating lubricating coating on an inner circumferential surface of a die cavity of a pressing mold; filling the die cavity of the pressing mold with raw material powder including a soft magnetic powder; compressing the raw material powder to form a green compact; and extruding the green compact from the die cavity, wherein the insulating lubricating coating formed on the inner circumferential surface of the die cavity of the pressing mold is formed in an area that is 20% to 80% of the total inner circumferential length along a circumferential direction that is an axis corresponding to the extrusion direction of the pressing mold. [8] The method for producing a powder compact for a magnetic core according to [7], wherein the insulating lubricating coating contains lubricating oil and insulating particles. [9] The method for producing a green compact for a magnetic core according to [8], wherein the insulating particles include at least one type selected from the group consisting of molybdenum disulfide particles and insulating ceramic particles.
[10] The method for producing a powder compact for a magnetic core according to any one of [7] to [9], wherein the insulating lubricating coating is formed over an area that is 50% or more and 100% or less of the total length of the pressing die in the extrusion direction.
[11] The method for producing a powder compact for a magnetic core according to any one of [7] to
[10] , wherein the insulating lubricating coating has a thickness of 1 μm to 20 μm. Effect of the Invention
[0014] According to one embodiment of the present disclosure, it is possible to provide a powder magnetic core having low core loss and excellent dimensional accuracy. [Brief description of the drawings]
[0015] [Figure 1] FIG. 2 is a schematic diagram illustrating a molding process in a compression molding method. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, one embodiment of the present invention will be described, but the present invention is not limited to the following examples.
[0017] The iron loss W of the powder magnetic core is the eddy current loss W e and hysteresis loss W h is the sum of the eddy current loss W e and hysteresis loss Wh are expressed by the following formula 1 and formula 2, respectively, so that the iron loss W is expressed by the following formula 3. In the formula, f is the frequency, B m is the excitation magnetic flux density, ρ is the resistivity, t is the thickness of the material, k 1 ,k 2 is a coefficient.
[0018] (Formula 1) W e =(k 1 B m 2 t 2 / ρ)f 2 (Formula 2) W h =k 2 B m 1.6 f (Formula 3) W=W e +W h =(k 1 B m 2 t 2 / ρ)f 2 +k 2 B m 1.6 f
[0019] As is clear from Equations 1 to 3, the eddy current loss W e Since increases in proportion to the square of the frequency f, in order to apply a powder magnetic core to a reactor or the like used in the high frequency range, the eddy current loss W e It is essential to suppress the eddy current loss W e In order to suppress eddy currents, it is necessary to confine the eddy currents to a small area. For this reason, in a dust core, the individual soft magnetic powder particles are configured to be insulated, thereby reducing the eddy current loss W e Therefore, if the particles of the soft magnetic powder communicate with each other, electrical conduction occurs through the communicated portions, generating large eddy currents, so it is important to ensure insulation between the individual soft magnetic powder particles.
[0020] In recent years, further improvement of magnetic properties has been demanded, and in order to improve the magnetic flux density, the compact is compressed at a higher pressure to increase the space factor of the soft magnetic powder. However, when the raw powder is compressed at a high pressure, the pressure (springback) that expands the compact toward the side direction also increases. When the compact, which is subject to the springback, is extracted from the mold hole, the side of the compact is strongly pressed against the inner peripheral surface of the mold hole when the compact slides against the mold hole. For this reason, plastic flow occurs in the surface layer of the side of the compact after it is extracted from the mold hole, and the insulating coating formed on the surface of the soft magnetic powder particles is destroyed, or the soft magnetic powder particles are conductive with each other, and the eddy current increases. When magnetic flux is generated in a closed magnetic circuit, the eddy current circulates in a ring shape perpendicular to the direction of the magnetic flux, centered on the magnetic flux. Normally, the increase in eddy currents can be suppressed by insulating each particle of the soft magnetic powder, but if the insulation is broken at the contact surface of the compact and the outer periphery of the compact becomes conductive, this can cause a significant increase in eddy currents. In particular, in the case of a reactor, the magnetic path is formed by combining magnetic cores, so there is a considerable amount of leakage of magnetic flux (fringing) from the combined surface. If the leaked magnetic flux re-enters the conductive contact surface in a direction perpendicular to the contact surface, the eddy currents can become even larger. Therefore, maintaining the insulation of the contact surface of the compact is one of the very important technical requirements for powder cores for high-frequency applications. Among powder core materials, low-alloy materials such as pure iron are particularly prone to plastic flow due to their soft base, and since they are material systems with low resistivity of the base, it is important to suppress the conduction caused by plastic flow.
[0021] The higher the frequency, the more the induced current generated in the powder core is concentrated on the surface. For this reason, if a powder core in which plastic flow occurs in the surface layer and the insulating coating of the soft magnetic powder particles is destroyed as described above is used in a high-frequency application such as a reactor, the induced current will be concentrated in the surface layer where the insulating coating is destroyed and the soft magnetic powder particles are conductive to each other, resulting in eddy current loss W e may become larger and cause an increase in iron loss W.
[0022] "Powder magnetic core" A powder magnetic core according to one embodiment is a compact formed by compression molding soft magnetic powder, and the sliding surface of the compact is characterized in that an area having a resistivity of 5 Ω·cm or more is 20% to 80% of the entire sliding surface, and an area having a resistivity of 1 Ω·cm or less is 20% to 80% of the entire sliding surface. This makes it possible to provide a dust core with low core loss and excellent dimensional accuracy.
[0023] By forming an area having a resistivity of 5 Ω·cm or more and an area having a resistivity of 1 Ω·cm or less on the sliding surface of the powder core, when the powder core is used as a high-frequency powder core in which induced currents flow concentratingly on the surface of the powder core, the provision of an area of high resistivity can reduce eddy current loss We. By specifying the area ratio of the area having a resistivity of 5 Ω·cm or more and the area having a resistivity of 1 Ω·cm or less, the insulation of the entire powder core can be maintained, an increase in iron loss can be prevented, and a decrease in dimensional accuracy can be prevented.
[0024] A powder magnetic core is a green compact obtained by compression molding soft magnetic powder. Compression molding is performed by filling raw material powder containing soft magnetic powder into a mold cavity and compressing it. The sliding surfaces are the surfaces where the green compact and the mold slide while the raw material powder is compressed in the mold, or while the compressed green compact is pushed out of the mold. Typically, a powder magnetic core produced by compression molding is formed as a green compact by filling a die cavity of a mold with raw material powder and compressing the raw material powder with a punch member through the opening of the die cavity. In one method, a mold having a through-hole-shaped die cavity is used to fill the die cavity with raw material powder, and punch members are inserted from both ends of the die cavity to compression mold the raw material powder. Then, by moving one of the punch members in a direction to push out the green compact, the green compact is pushed out from the opening of the die cavity while sliding against the inner peripheral surface of the mold. In compression molding, the surface of the green compact that comes into contact with the punch member is also called the punch surface. Considering that the powder magnetic core produced by compression molding is uniformly pressed by the punch member in the die hole and is extruded from the die hole by the punch member, it is preferable that the powder magnetic core has a side surface parallel to the extrusion direction. The side surface parallel to the extrusion direction becomes the sliding surface. It is also preferable that the powder magnetic core has a pair of surfaces intersecting the extrusion direction. The pair of surfaces becomes the punch surface. The side surface parallel to the extrusion direction may be a flat surface or a curved surface, or may be a surface having a flat surface and a curved surface. The cross-sectional shape perpendicular to the extrusion direction may be a polygon such as a triangle, a rectangle, a pentagon, or a shape in which the corners of these polygons have an R structure, an ellipse, a circle, or the like, or a shape in which a recess and / or a protrusion is formed. It is preferable that the punch surfaces, which are both end surfaces intersecting the extrusion direction, have these cross-sectional shapes.
[0025] An example of a compression molding method for producing a powder magnetic core will be described with reference to Fig. 1. Fig. 1 is a schematic diagram for explaining the compression molding method. In FIG. 1, 1 is a mold, 2 is a lower punch member, 3 is an upper punch member, and 4 is a feeder. The mold 1 has a through-hole-shaped mold hole 1a, and the lower punch member 2 and the upper punch member 3 have a cross-sectional shape that fits into the inner peripheral surface of the mold hole 1a. In FIG. 1(a), the lower punch member 2 is inserted from the lower opening of the mold hole 1a of the mold 1, and the raw material powder M is filled into the mold hole 1a from the upper opening of the mold hole 1a using the feeder 4. In FIG. 1(b), with the raw material powder filled in the mold hole 1a, the upper punch member 3 is inserted from the upper opening of the mold hole 1a, and the upper punch member 3 and the lower punch member 2 are each pushed in the depth direction of the mold hole 1a to pressurize the raw material powder M and compress it. As a result, a green compact C is formed in the mold hole 1a. 1(c), the upper punch member 3 is removed from the die hole 1a, and the lower punch member 2 is pushed into the die hole 1a in the depth direction, i.e., in the extrusion direction, and the powder compact C is extracted from the die hole 1a. In this manner, a powder magnetic core can be obtained.
[0026] Since the magnetic flux density of the powder magnetic core is increased by compressing and molding soft magnetic powder at a high density, a high density powder magnetic core is preferable. The density ratio of the powder magnetic core is preferably 90% or more, more preferably 90.5% or more, and even more preferably 91% or more. The density ratio of the powder magnetic core is not particularly limited, but may be 98% or less, and further may be 95% or less, when a typical compression molding device is used. The density ratio of the powder magnetic core is measured based on the density of a material of the same composition as the powder magnetic core in a pore-free state. The density can be measured in accordance with JIS K 0061:2001.
[0027] Since high-density powder cores are compressed under high pressure, frictional resistance between the inner circumferential surface of the die cavity and the sliding surface of the compact may cause plastic flow to occur on the sliding surface of the resulting powder core. The area where plastic flow occurs on the sliding surface of the powder core may have a reduced resistivity due to the soft magnetic powder particles bonding together to produce electrical conductivity, or the individual particles of the soft magnetic powder being broken to expose the conductive parts inside the particles. In order to suppress the occurrence of plastic flow on the sliding surface of the compact, there is a method of applying a lubricating component to the inner circumferential surface of the die cavity to reduce the frictional resistance between the inner circumferential surface of the die cavity and the sliding surface of the compact. The sliding surface of the powder core obtained by this method can provide a state in which the occurrence of plastic flow is suppressed and insulation is maintained. Furthermore, since the lubricating component itself has insulating properties, when an insulating coating is formed on the sliding surface of the powder core by the lubricating component, a state in which the insulation of the compact is further enhanced can be provided.
[0028] When attempting to obtain a high-density powder magnetic core, if a lubricant is not applied to the inner peripheral surface of the mold cavity in the compression molding, frictional resistance occurs between the inner peripheral surface of the mold cavity and the sliding surface of the powder compact, and plastic flow occurs on the sliding surface of the powder compact, which may lead to a decrease in resistivity. If the resistivity of the sliding surface of the powder core decreases, eddy current loss occurs, leading to an increase in iron loss. By applying a lubricant to the inner peripheral surface of the mold cavity, the occurrence of plastic flow on the sliding surface of the powder compact is suppressed, making it possible to maintain or improve the insulation of the sliding surface of the powder compact, but if an excessive lubricant is applied to the sliding surface of the powder compact, the dimensional accuracy of the resulting powder magnetic core may decrease.
[0029] In one embodiment, the powder magnetic core preferably has a region having a resistivity of 5 Ω·cm or more occupying 20% or more of the entire sliding contact surface. The region having a resistivity of 5 Ω·cm or more is a region exhibiting high resistivity, which can increase the resistivity of the powder magnetic core and prevent an increase in iron loss. When the entire sliding surface of the powder core has high resistivity, an increase in iron loss of the powder core can be prevented. According to one embodiment, if the sliding surface of the powder core has partial high resistivity, an increase in iron loss of the powder core can be prevented even if part of the sliding surface of the powder core includes an area of low resistivity.
[0030] The region having a resistivity of 5 Ω·cm or more is preferably a region that exhibits high resistivity and where plastic flow is not observed on the sliding surface. The region having a resistivity of 5 Ω·cm or more is preferably a region where frictional resistance is reduced and the occurrence of plastic flow is suppressed on the sliding surface. For example, the region having a resistivity of 5 Ω·cm or more is preferably a region where the compact is extruded with a lubricant component interposed between the inner circumferential surface of the mold cavity and the sliding surface of the compact. In this region, frictional resistance is reduced and the occurrence of plastic flow is suppressed, so that bonding between particles of the soft magnetic powder is prevented, and a decrease in resistivity can be prevented. In addition, by forming a coating of the lubricant component on the sliding surface of the compact, the resistivity can be reduced due to the insulating properties of the lubricant component itself. In addition, the resistivity can also be reduced by the presence of insulating particles between adjacent particles of the soft magnetic powder.
[0031] The area having a resistivity of 5 Ω cm or more is preferably 20% or more of the entire sliding surface area, may be 40% or more, or may be 60% or more, thereby preventing an increase in iron loss in the entire powder magnetic core. The area having a resistivity of 5 Ω·cm or more is preferably 80% or less of the entire sliding surface, more preferably 70% or less, and even more preferably 50% or less, and may be 30% or less, thereby preventing a decrease in the dimensional accuracy of the powder magnetic core. The region having a resistivity of 5 Ω cm or more on the sliding surface of the powder magnetic core may be one region or two or more regions. When the sliding surface of the powder magnetic core has two or more regions having a resistivity of 5 Ω cm or more, it is preferable that the total of the two or more regions is in the above range.
[0032] The powder magnetic core preferably has a resistivity of 5 Ω·cm or more in an area of 20% or more of the entire sliding surface, more preferably 20 Ω·cm or more, and even more preferably 50 Ω·cm or more. By partially increasing the resistivity of the sliding surface of the powder magnetic core, an increase in iron loss of the entire powder magnetic core can be prevented.
[0033] In one embodiment, the sliding contact surface of the powder magnetic core preferably has a region having a resistivity of 1 Ω·cm or less that occupies 20% or more by area of the entire sliding contact surface. The region with a resistivity of 1 Ω·cm or less is a region that exhibits low resistivity. By having the entire sliding surface of the powder core be highly resistive, it is possible to prevent an increase in the iron loss of the powder core, but this can result in a decrease in the dimensional accuracy of the powder core. In contrast, by having a low resistivity region within a specified area included in part of the sliding surface of the powder core, it is possible to improve the dimensional accuracy of the powder core while preventing an increase in iron loss.
[0034] The region having a resistivity of 1 Ω·cm or less is preferably a region that exhibits low resistivity and where plastic flow is observed on the sliding surface. For example, the region having a resistivity of 1 Ω·cm or less is preferably a region in which the green compact is compression molded without the presence of solid lubricant components such as molybdenum disulfide between the inner circumferential surface of the mold cavity and the sliding surface of the green compact. In this region, frictional resistance increases, plastic flow is likely to occur, and resistivity tends to decrease. In addition, the influence of insulating lubricant components is eliminated, and resistivity is unlikely to increase. In order to achieve low resistivity, it is preferable that the proportion of insulating particles interposed between the particles of the soft magnetic powder is small.
[0035] The area having a resistivity of 1 Ω cm or less preferably accounts for 20% or more of the entire sliding surface, more preferably 30% or more, and even more preferably 30% or more, and may be 50% or more, thereby preventing a decrease in the dimensional accuracy of the powder magnetic core. The area having a resistivity of 1 Ω cm or less is preferably 80% or less of the entire sliding surface, but may be 60% or less, or may be 40% or less, thereby preventing an increase in iron loss of the powder magnetic core. The region having a resistivity of 1 Ω cm or less on the sliding surface of the powder magnetic core may be one region or two or more regions. When the sliding surface of the powder magnetic core has two or more regions having a resistivity of 1 Ω cm or less, it is preferable that the total of the two or more regions is in the above range.
[0036] The powder magnetic core preferably has a resistivity of 1 Ω cm or less over 20% by area or more of the entire sliding surface, and more preferably has a resistivity of 0.5 Ω cm or less. By partially lowering the resistivity of the sliding surface of the powder magnetic core, it is possible to prevent a decrease in the dimensional accuracy of the powder magnetic core.
[0037] The resistivity of the powder core can be measured by a four-point probe method. The terminal row is preferably arranged on the sliding surface so as to be parallel to the sliding direction of the powder core, and the measurement is preferably performed. The measurement points of the resistivity of the powder core may be appropriately set according to the size of the sliding surface, but it is preferable that the measurement points are 4 to 100 positions, more specifically 10 to 50 positions, at equal intervals in the circumferential direction of the sliding surface. According to the manufacturing method of the powder core described later, the measurement points of the resistivity of the powder core in the extrusion direction are almost constant over the entire length of the extrusion direction of the powder core, and the measurement points of the resistivity of the powder core in the extrusion direction may be 1 to 3 positions, or may be 1 position. In the case of a powder core whose resistivity in the extrusion direction changes, it may be appropriately set according to the size of the sliding surface, but it is preferable that the measurement points of the resistivity of the powder core are 2 to 50 positions at equal intervals in the extrusion direction of the sliding surface.
[0038] The area ratio of the resistivity of the powder magnetic core can be obtained by measuring the resistivity at equal intervals around the circumference of the sliding surface of the powder magnetic core and calculating it according to the following method. The resistivity is preferably measured according to the four-probe method described above. The area ratio where the resistivity is 5 Ωcm or more can be calculated by ((measurement points where the surface resistivity is 5 Ωcm or more) / (total measurement points))×100(%). The area ratio where the surface resistivity is 1 Ωcm or less can be calculated by ((measurement points where the surface resistivity is 1 Ωcm or less) / (total measurement points))×100(%).
[0039] The soft magnetic powder will now be described. As the soft magnetic powder, soft magnetic iron powder, soft magnetic iron alloy powder, etc. are preferable. For example, iron-based metal powder containing iron or iron alloy such as pure iron, Fe-Si alloy, Fe-Al alloy, permalloy, sendust, permendur, soft ferrite, amorphous magnetic alloy, nanocrystalline magnetic alloy, etc. may be mentioned. These may be used alone or in combination of two or more. In terms of high magnetic flux density, moldability, etc., pure iron powder can be preferably used. The soft magnetic powder may be either a soft powder or a hard powder. It is preferable to use a soft magnetic powder in order to form regions with different resistivities on the sliding surface of the powder magnetic core by suppressing the occurrence of plastic flow in a region having a resistivity of 5 Ω·cm or more on the sliding surface of the powder magnetic core and promoting plastic flow in a region having a resistivity of 1 Ω·m or less. Soft magnetic powders are prone to plastic flow during compression molding, but by partially performing a treatment to suppress the occurrence of plastic flow, it is possible to partially suppress the occurrence of plastic flow on the sliding surface of the powder magnetic core, thereby forming regions with different resistivities. Examples of soft magnetic powders include pure iron powder and iron-based low-alloy powders containing 3 mass% or less of alloy elements such as Si and Al. When using a soft magnetic powder that is not prone to plastic flow but is not hard enough to break, if it is possible to form an area with a resistivity of 1 Ω m or less without the occurrence of plastic flow on the sliding surface of the compact, it is possible to form an area with a resistivity of 5 Ω m or more by partially adhering insulating particles, which will be described later, to the sliding surface of the compact.
[0040] The average particle size of the soft magnetic powder is preferably 1 to 300 μm, which makes it possible to obtain a high density dust core suitable for high frequencies. The average particle size of the soft magnetic powder is preferably 1 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more. The average particle size of the soft magnetic powder is preferably 300 μm or less, more preferably 200 μm or less, and even more preferably 100 μm or less. The average particle size of the soft magnetic powder can be measured, for example, by a laser diffraction method. A laser diffraction type particle size distribution measuring device (for example, "MT3300EX II" manufactured by Microtrack Bell Co., Ltd.) can be used for the measurement. Here, the average particle size indicates the median diameter (D50) in the volume-based particle size distribution.
[0041] The soft magnetic powder may be a soft magnetic powder having an insulating coating covering the surface. This can ensure the insulation of each particle of the soft magnetic powder. Each particle of the soft magnetic powder may be entirely or partially covered with an insulating coating, but from the viewpoint of insulation, it is preferable that the entire surface is covered with an insulating coating. Examples of the insulating coating include inorganic insulating coatings such as phosphoric acid-based chemical coatings, silicone resin coatings, etc. The method of coating each particle of the soft magnetic powder with an insulating coating may be formed by chemical conversion treatment or contact coating according to a normal method, and for example, the descriptions in Japanese Patent No. 4044591 and Japanese Patent No. 4927983 can be referred to. The soft magnetic powder having an insulating coating may be appropriately selected from commercially available powder products, and examples thereof include Somaloy110i (5P) manufactured by Höganäs AB and MH20D manufactured by Kobe Steel, Ltd.
[0042] The powder magnetic core may be produced by compression molding using raw material powder obtained by mixing a soft magnetic powder with optional additives, such as a binder such as a resin, a molding lubricant, insulating ceramic particles, etc. The binder such as resin can improve the moldability of the green compact, and also helps to ensure the insulation of each particle of the soft magnetic powder. The binder can be used in combination with both soft magnetic powder having an insulating coating and soft magnetic powder not having an insulating coating. For example, even when using soft magnetic powder not having an insulating coating, it is possible to ensure the insulation of each particle of the soft magnetic powder by using a binder or the like. The resin blended as a binder is preferably 2 mass % or less based on the total amount of the powder core, which can increase the space factor of the soft magnetic powder in the powder core to prevent a decrease in magnetic flux density.
[0043] In the sliding contact surface of the powder magnetic core, a region having a resistivity of 5 Ω·cm or more preferably has a surface layer portion in which insulating particles are present between the particles of the soft magnetic powder. In this disclosure, the surface layer portion of a powder magnetic core refers to a portion up to a depth of 100 μm from the surface of the powder magnetic core. The same applies hereinafter.
[0044] In the surface layer of the sliding surface of the powder magnetic core, the insulating particles are interposed between the particles of the soft magnetic powder, thereby supporting the soft magnetic powder particles and suppressing the deformation and plastic flow of the soft magnetic powder particles. This prevents insulation breakdown due to conduction between the particles of the soft magnetic powder, exposure of the conductive parts inside the particles due to the destruction of each particle of the soft magnetic powder, etc., and forms a region with high resistivity. The insulating properties of the insulating particles themselves can also increase the resistivity of the sliding surface of the powder magnetic core.
[0045] In the region of the sliding surface of the powder magnetic core having a resistivity of 5 Ω cm or more, adjacent particles of the soft magnetic powder are preferably in a discontinuous state due to the presence of insulating particles between them, thereby preventing electrical conduction between the particles of the soft magnetic powder and forming a region with a higher resistivity.
[0046] The insulating particles preferably include at least one type selected from the group consisting of molybdenum disulfide particles and insulating ceramic particles, and it is preferable to include molybdenum disulfide particles because they have a lubricating effect as well as insulating properties. For example, in the surface layer portion of the powder magnetic core, a region having a resistivity of 5 Ω·cm or more preferably contains molybdenum disulfide particles alone or a combination of molybdenum disulfide particles and insulating ceramic particles between particles of the soft magnetic powder.
[0047] In a powder core obtained by compression molding a raw material powder containing soft magnetic powder having an insulating coating covering the surface, the absence of plastic flow prevents destruction of the insulating coating on the surface of the soft magnetic powder particles, and a powder core can be obtained in which the soft magnetic powder particles are well maintained in a state where they are covered with the insulating coating. By covering the soft magnetic powder with an insulating coating and having insulating particles between the soft magnetic powder particles, higher insulation can be obtained. Even if the soft magnetic powder does not have an insulating coating, a powder core obtained by compression molding a raw material powder containing a soft magnetic powder and a binder such as a resin can have insulating particles pressed between the particles of the soft magnetic powder on the sliding surface of the powder core because plastic flow does not occur. The presence of the binder and insulating particles between the particles of the soft magnetic powder makes it possible to obtain a higher insulation property.
[0048] When the sliding surface of such a powder magnetic core is observed by, for example, electron probe microanalysis (EPMA), it is possible to observe in the component map that insulating particles are present in the gaps between the particles of the soft magnetic powder. It can also be observed by surface observation by SEM-EDX.
[0049] The insulating particles preferably have a maximum particle size of 10 nm to 1000 nm. The molybdenum disulfide particles preferably have a maximum particle size of 1000 nm or less.The molybdenum disulfide particles preferably have a maximum particle size of 10 nm or more, more preferably 100 nm or more. As the insulating ceramic particles, ceramic particles such as oxide-based, nitride-based, and carbide-based particles can be used. The insulating ceramic particles may be surface-modified. Details are described below. The insulating ceramic particles preferably have a maximum particle size of 1000 nm or less, and more preferably have a maximum particle size of 10 nm or more, and more preferably have a maximum particle size of 50 nm or more. The maximum particle size of the insulating particles can be determined by measuring the long axis of the particles in a composition map by electron probe microanalysis. The measurement area should be set to an area that contains at least 10 insulating particles.
[0050] It is preferable that the occurrence of plastic flow be observed in an area of the sliding surface of the powder magnetic core having a resistivity of 1 Ω·cm or less. On the sliding surface of the powder magnetic core, the region having a resistivity of 1 Ω·cm or less preferably has a smaller number of insulating particles per unit area in the surface layer portion than the region having a resistivity of 5 Ω·cm or less. When plastic flow occurs in an area of the sliding surface of a powder magnetic core having a resistivity of 1 Ω·cm or less, the insulation property decreases, and an area of low resistivity can be formed. Also, since an area of the sliding surface of a powder magnetic core having a resistivity of 1 Ω·cm or less is an area with decreased insulation property, it is preferable that there are no insulating particles or that the proportion of insulating particles is small.
[0051] In the region of the sliding surface of the powder magnetic core having a resistivity of 5 Ω·cm or more, the area ratio of insulating particles is preferably 30% or more in a component map obtained by electron probe microanalysis.
[0052] In the sliding surface of the powder magnetic core, the area having a resistivity of 5 Ω·cm or more is preferably an area ratio of insulating particles of 30% or more, more preferably 40% or more, and even more preferably 50% or more, in a composition map obtained by electron probe microanalysis (EPMA). This allows a sufficient amount of insulating particles to be present between the particles of the soft magnetic powder, which further suppresses the occurrence of plastic flow in this area, forming an area of high resistivity. If plastic flow occurs, electrical conduction between the particles of the soft magnetic powder may occur, and the conductive parts may be exposed due to the destruction of individual particles of the soft magnetic powder, which may reduce the resistivity. As the area ratio of the insulating particles on the sliding surface of the powder magnetic core increases, the volume ratio of the soft magnetic powder on the sliding surface decreases, but this is only the state of the surface layer of the sliding surface of the powder magnetic core, and in the interior of the powder magnetic core deeper than the surface layer, the volume ratio of the soft magnetic powder is increased to a desired volume ratio depending on the composition of the raw material powder, the degree of compression, etc. Therefore, there is no particular upper limit to the area ratio of the insulating particles on the surface layer of the sliding surface of the powder magnetic core, and the sliding surface of the powder magnetic core may be completely covered with insulating particles. When the sliding surface of the powder magnetic core is covered with a thin layer of insulating particles, when the thin layer is removed and the surface of the surface layer is observed, the area ratio of the insulating particles interposed between the particles of the soft magnetic powder is generally in the range of about 65% or less.
[0053] Examples of insulating particles include molybdenum disulfide particles, insulating ceramic particles, etc. When two or more types of insulating particles are contained in a region having a resistivity of 5 Ω·cm or more, it is preferable that the total amount of the two or more types of insulating particles satisfies the above area ratio.
[0054] The component map by electron probe microanalysis is obtained by wavelength dispersive spectroscopy (WDS) under the following measurement conditions: acceleration voltage 15 kV, sample current 100 nA, measuring time 5 msec, area size 604 × 454 μm. The component map can be an image with a magnification of 500 times. The component map is binarized so that the insulating particles can be separated from the other parts and identified, and the binarized image can be used to determine the area ratio (%) of the insulating particles. Commercially available software can be used as the image analysis software used for binarization. For example, "WinROOF" by Mitani Shoji Co., Ltd. can be used.
[0055] When measuring the area ratio of insulating particles by electron probe microanalysis in a state where insulating particles including molybdenum disulfide particles and insulating ceramic particles are observed on the sliding surface of a powder magnetic core, it is important to take into consideration the affinity of the molybdenum disulfide particles and insulating ceramic particles for the soft magnetic powder. When there is no difference or almost no difference in the affinity between the molybdenum disulfide particles and the insulating ceramic particles for the soft magnetic powder, the molybdenum disulfide particles and the insulating ceramic particles will each penetrate equally between the particles of the soft magnetic powder during compression molding, and will also be mixed in the gaps between the particles of the soft magnetic powder on the component map, so the condition of the surface layer can be evaluated based on the area ratio of the total amount of the molybdenum disulfide particles and the insulating ceramic particles. On the other hand, when the affinity for the soft magnetic powder is different between the insulating ceramic particles and the molybdenum disulfide particles, the particles with high affinity cover the particles of the soft magnetic powder and the particles with low affinity are present around them, so that in the component map, the particles with low affinity are unevenly distributed in the area corresponding to the gaps between the particles of the soft magnetic powder, and the particles with high affinity are unevenly distributed in the area of the soft magnetic powder and the nearby area surrounding it. Therefore, in order to evaluate the particles interposed between the particles of the soft magnetic powder in the surface layer part of the sliding surface of the powder core, it is considered more appropriate to evaluate based on the area ratio of the particles with low affinity for the soft magnetic powder. Such differences in affinity are largely due to the type of insulating coating formed on the surface of the particles of the soft magnetic powder and the presence or absence and type of surface modification applied to the insulating ceramic particles.
[0056] In the powder magnetic core, the sliding contact surface preferably has a region having the resistivity as described above, but the resistivity of both end faces (punch surfaces) intersecting the extrusion direction is not particularly limited. Since the punch surface of the powder magnetic core does not slide against the molding die or punch member, the surface of the punch surface may be in a state where the occurrence of plastic flow is hardly observed, and may be a region that maintains insulation and has high resistivity. Since the punch surface of the powder magnetic core does not slide against the molding die or punch member, there is no need to attach an external lubricating component, and therefore lubricating oil, insulating particles, etc. may not be observed on the punch surface.
[0057] "Method of manufacturing magnetic core powder compacts" A method for producing a green compact for a magnetic core according to one embodiment includes forming an insulating lubricating coating on the inner circumferential surface of a die cavity of a pressing mold, filling the die cavity with raw material powder including soft magnetic powder, compressing the raw material powder to form a green compact, and extruding the green compact from the die cavity, and is characterized in that the insulating lubricating coating formed on the inner circumferential surface of the die cavity of the pressing mold is formed in an area that is 20% to 80% of the total inner circumferential length along a circumferential direction that is an axis along the extrusion direction of the pressing mold. According to this, it is possible to provide a powder magnetic core having low iron loss and excellent dimensional accuracy. The powder magnetic core according to the above-mentioned embodiment can be manufactured by following the method for manufacturing a powder compact for a magnetic core according to one embodiment, but the powder magnetic core according to the above-mentioned embodiment is not limited to one manufactured by the following manufacturing method.
[0058] A method for forming an insulating lubricating coating on the inner peripheral surface of a die cavity of a molding die will be described below. The molding die is not particularly limited and can be prepared appropriately according to the shape and dimensions of the powder magnetic core, and is preferably made of metal. The molding die may have a through-hole portion and may have a structure in which punch members are inserted from both ends of the through-hole portion. For example, the molding die may have the structure shown in FIG. 1.
[0059] The insulating lubricating coating formed on the inner circumferential surface of the mold cavity of the pressing die is preferably formed over an area of 20% to 80% of the entire inner circumferential length in the circumferential direction, the axis being the extrusion direction of the pressing die. By setting this area to 20% or more and 80% or less, the raw material powder filled in the cavity of the pressing die comes into contact with the insulating lubricating coating over at least 20% or more of the cavity, and does not come into contact with the insulating lubricating coating over at least 20% or more of the cavity. Alternatively, when the raw material powder filled in the cavity of the pressing die is compressed and the green compact is pushed out of the cavity, the insulating lubricating coating and the green compact come into contact over at least 20% or more of the cavity, and do not come into contact with each other over at least 20% or more of the cavity. The insulating lubricating coating formed on the inner peripheral surface of the cavity of the mold is preferably 20% or more, 40% or more, 60% or more, or even 80% of the total inner peripheral length along the circumferential direction with the extrusion direction of the mold as the axis. This allows a high resistivity region to be formed in 20% or more of the sliding surface of the obtained green compact. When the green compact is compression molded, the insulating lubricating coating is interposed between the inner peripheral surface of the cavity and the sliding surface of the green compact, so that the insulating lubricating coating acts as a lubricant, suppressing the occurrence of plastic flow on the sliding surface in that region and preventing a decrease in insulation. In addition, the insulating component of the insulating lubricating coating is applied from the inner peripheral surface of the cavity to the sliding surface of the green compact, thereby further improving the insulation of the sliding surface of the green compact. The insulating lubricating coating formed on the inner peripheral surface of the mold cavity of the mold is preferably 80% or less, more preferably 60% or less, even more preferably 40% or less, and may be 20% of the entire inner peripheral length along the circumferential direction with the extrusion direction of the mold as the axis. This allows a low resistivity region to be formed in 20% or more of the sliding surface of the obtained green compact. When the green compact is compression molded, since the insulating lubricating coating is not interposed between the inner peripheral surface of the mold cavity and the sliding surface of the green compact, plastic flow occurs due to frictional resistance with the inner peripheral surface of the mold cavity at the sliding surface of the region, and conduction occurs between the particles of the soft magnetic powder, leading to a decrease in resistivity. Alternatively, the insulation of each particle of the soft magnetic powder is destroyed due to frictional resistance with the inner peripheral surface of the mold cavity at the sliding surface of the region, causing conduction between the particles of the soft magnetic powder, leading to a decrease in resistivity.
[0060] The insulating lubricating coating is preferably formed in a region that is 20% to 80% of the entire inner circumference along the circumferential direction, with the extrusion direction of the mold as the axis, but may be formed in one region along the circumferential direction, or in two or more regions. If formed in two or more regions, the total circumferential length of the two or more regions should be 20% to 80% of the entire inner circumference.
[0061] The insulating lubricating coating is preferably formed on the inner circumferential surface of the mold cavity of the pressing die over an area that is 50% to 100% of the total length of the pressing die in the extrusion direction. Since the green compact is extruded while sliding in the extrusion direction relative to the mold cavity, if an insulating lubricating coating is partially formed on the inner circumferential surface of the mold cavity in the extrusion direction, the insulating lubricating coating will come into contact with the green compact along the extrusion direction. The area in which the insulating lubricating coating is formed relative to the entire length of the pressing mold in the extrusion direction is preferably 50% or more, more preferably 80% or more, even more preferably 90% or more, and may be 100%, which can further promote contact of the insulating lubricating coating with the sliding surface of the green compact. The region where the insulating lubricating coating is formed over the entire length of the mold in the extrusion direction is preferably formed downstream in the direction in which the green compact is extruded from the mold. For example, the region where the insulating lubricating coating is formed over the entire length of the mold in the extrusion direction is preferably a region that includes the end on the downstream side in the direction in which the green compact is extruded from the mold, and is preferably a region that is 50% or more of the entire length in the extrusion direction starting from the end. As a result, while the green compact is being extruded from the mold, the inner circumferential surface of the mold cavity and the green compact move relatively to each other, so that the insulating lubricating coating comes into contact with the entire length of the green compact in the extrusion direction. Thus, a green compact can be obtained in which the insulating lubricating coating is attached over the entire length in the extrusion direction.
[0062] The insulating lubricating coating is preferably formed in an area that is 50% to 100% of the total length of the mold in the extrusion direction, but may be formed in one area along the extrusion direction, or in two or more areas. If it is formed in two or more areas, the total length of the two or more areas in the extrusion direction should be 50% to 100% of the total length of the mold in the extrusion direction.
[0063] The insulating lubricating coating preferably contains lubricating oil and insulating particles. The insulating particles mixed in the insulating lubricating coating exhibit insulating properties, and therefore can act to maintain the electrical insulation of the soft magnetic powder on the sliding surface of the compact when attached to the sliding surface of the compact. When the insulating particles are harder particles, when the insulating particles are attached to the sliding surface of the compact and the inner circumferential surface of the die cavity slides against the compact, the insulating particles penetrate and intervene between the particles of the soft magnetic powder on the sliding surface of the compact, and support the individual particles of the soft magnetic powder, thereby suppressing the occurrence of plastic flow. The insulating particles are preferably insulating particles having a lubricating effect. The insulating particles having a lubricating effect function as a solid lubricant themselves, and are therefore useful for reducing the frictional resistance between the inner circumferential surface of the die cavity and the compact. The insulating particles may include at least one selected from the group consisting of molybdenum disulfide particles and insulating ceramic particles. The insulating lubricating coating preferably includes a lubricating oil and molybdenum disulfide particles, or a lubricating oil, molybdenum disulfide particles, and insulating ceramic particles. From the viewpoint of excellent lubricating action, it is preferable that the insulating lubricating coating includes molybdenum disulfide particles.
[0064] When an insulating lubricating coating containing molybdenum disulfide particles is formed on the inner peripheral surface of a die cavity, the molybdenum disulfide particles penetrate and are interposed between the particles of soft magnetic powder on the sliding surface of the powder compact when the powder compact is compression molded in the die cavity. When the powder compact is extruded from the die cavity in this state, the molybdenum disulfide particles support the individual particles of the soft magnetic powder against the frictional resistance caused by the extrusion, and act to suppress the deformation and plastic flow of the particles. Furthermore, the molybdenum disulfide particles can relieve the stress caused by the frictional resistance applied to the soft magnetic powder particles due to their own cleavage and lubricity. When an insulating lubricating coating containing molybdenum disulfide particles and insulating ceramic particles is formed on the inner surface of a mold cavity, when the powder compact is extruded from the mold cavity, the insulating ceramic particles, which are harder than the molybdenum disulfide particles, support the individual particles of the soft magnetic powder and resist the stress if the stress exceeds the level at which the molybdenum disulfide particles can be alleviated, and the insulating ceramic particles undergo brittle fracture if the stress is excessive, thereby alleviating the stress on the soft magnetic powder particles. The presence of lubricating oil and molybdenum disulfide particles between the inner surface of the die cavity and the sliding surface of the powder compact reduces the frictional resistance between the inner surface of the die cavity and the sliding surface of the powder compact due to the lubricating properties of these particles, making it easier to remove the powder compact from the die cavity, and suppresses the occurrence of plastic flow at the sliding surface of the powder compact, maintaining the insulating properties of the soft magnetic powder, resulting in a powder core having an area of high resistivity.
[0065] Molybdenum disulfide particles have a moderate hardness and excellent insulating properties, so that when the compact is extruded from the die cavity, they penetrate between the particles of the soft magnetic powder on the sliding surface of the compact, thereby supporting the soft magnetic powder particles on the sliding surface of the compact and suppressing the occurrence of plastic flow, and the electrical insulation of the soft magnetic powder particles can be maintained. Furthermore, molybdenum disulfide particles function as a solid lubricant and are a lubricating material with high stress relaxation ability. The hardness of molybdenum disulfide (Vickers hardness: about 500 to 900 HV) is about the same as that of ceramics with a relatively low hardness, and they support the soft magnetic powder particles by being interposed between the particles of the soft magnetic powder against the stress due to frictional resistance, thereby suppressing the occurrence of plastic flow. Molybdenum disulfide particles have zero fracture strain, so that they can cleave themselves to relieve the stress on the soft magnetic powder particles when subjected to excessive stress. When molybdenum disulfide particles and insulating ceramic particles are used in combination, the molybdenum disulfide particles generally cleave prior to the insulating ceramic particles when subjected to stress.
[0066] The molybdenum disulfide particles preferably have a maximum particle size of 1000 nm or less. This allows the molybdenum disulfide particles to be dispersed and interposed between the particles of the soft magnetic powder by eliminating coarse particles, thereby better maintaining the insulation of the green compact. In addition, since the mass of individual molybdenum disulfide particles increases when they become coarse, eliminating the coarse particles can prevent the molybdenum disulfide particles from falling off the insulating lubricating coating formed on the inner peripheral surface of the die hole. The maximum particle size of the molybdenum disulfide particles is preferably 10 nm or more, and more preferably 100 nm or more, which makes it possible to eliminate excessively fine particles and to facilitate the formation of an insulating lubricating coating and the handling of the raw material.
[0067] As the insulating ceramic particles, ceramic particles such as oxide-based, nitride-based, and carbide-based particles can be used. As the oxide-based ceramic particles, aluminum oxide (Al 2 O 3 ), titanium dioxide (TiO 2 ), silicon dioxide (SiO 2), Magnesium oxide (MgO), Zirconium dioxide (ZrO 2 ), steatite (MgO SiO 2 ), zircon (ZrSiO 4 ), Ferrite (M 2 +O·Fe 2 O 3 ), Mullite (3Al 2 O 3 2SiO 2 ), forsterite (2MgO SiO 2 ), yttria (Y 2 O 3 ) and the like. Examples of nitride ceramic particles include aluminum nitride (AlN), titanium nitride (TiN), silicon nitride (Si 3 N 4 Examples of carbide ceramic particles include titanium carbide (TiC) and tungsten carbide (WC). Other examples include oxynitride ceramic particles such as sialon (Si-Al-ON compound), carbonitride ceramic particles such as titanium carbonitride (TiCN), cordierite particles, and machinable ceramics (SiO 2 ·Al 2 O 3 Alternatively, particles of AlN·BN or the like can be used. The insulating ceramic particles described above can be used alone or in combination of two or more types, and particles of the same type but different sizes can also be used in combination. Such ceramics have a yield stress of about 2000 to 10000 MPa, which is greater than that of low alloy steels, which have a yield stress of about 200 to 2000 MPa, and therefore can support soft magnetic powder particles against stress due to frictional resistance and suppress the occurrence of plastic flow. Furthermore, such ceramics have a moderate hardness (Vickers hardness) of about 200 to 1800 and a fracture strain of zero, so that when subjected to excessive stress, they can break by brittle fracture and disperse and relieve the stress on the soft magnetic powder particles. As described later, fine insulating ceramic particles are suitable, but fine powders have the possibility of dust explosions, so in this regard, it is preferable to use oxide-based insulating ceramic particles that are sufficiently oxidized and have a low possibility of dust explosions.
[0068] The insulating ceramic particles preferably have a maximum particle diameter of 1000 nm or less. This allows the insulating ceramic particles to be dispersed and interposed between the particles of the soft magnetic powder by excluding the coarse particles, so that the insulating properties of the green compact can be better maintained. In addition, since the mass of each insulating ceramic particle increases when it becomes coarse, by excluding the coarse particles, it is possible to prevent the insulating ceramic particles from falling off from the insulating lubricating coating formed on the inner peripheral surface of the mold hole. In addition, by excluding the coarse particles, when the green compact is extruded from the mold hole, the stress relaxation due to the self-rupture of the insulating ceramic particles acts more effectively, and the deformation of the soft magnetic powder particles can be more suppressed, and further, the inner peripheral surface of the mold hole can be prevented from being worn by the coarse particles. In addition, by excluding the coarse particles, it is possible to prevent the insulating coating formed on the particle surface of the soft magnetic powder from being destroyed when the green compact is extruded from the mold hole. In addition, the coarse particles may cause wear powder due to wear of the mold hole or the green compact, and the generation of this wear powder can be suppressed. This wear powder adheres to the surface of the powder compact and bonds the particles of the soft magnetic powder together, which can cause insulation breakdown between the particles of the soft magnetic powder. The insulating ceramic particles preferably have a maximum particle size of 10 nm or more, more preferably 50 nm or more, which makes it possible to eliminate excessively fine particles and facilitate the formation of an insulating lubricating coating and the handling of the raw materials.
[0069] The insulating ceramic particles may be surface-modified. Surface-modified, lipophilic insulating ceramic particles can be preferably used as described below.
[0070] The particle size of the insulating particles contained in the insulating lubricating coating is substantially the same as the particle size of the raw material of the insulating particles before it is added to the insulating lubricating coating. The maximum particle size of the raw material of the insulating particles can be measured by laser diffraction for powders in the μm unit, and can be measured by SEM observation or TEM observation for powders in the nm unit. In SEM observation or TEM observation, the maximum particle size can be determined based on the major axis of the particles in a measurement area where at least 10 particles are observed.
[0071] The green compact compressed using a die cavity having an insulating lubricating coating formed on its inner circumferential surface preferably has a structure in which insulating particles are present between the particles of the soft magnetic powder in the surface layer portion of the sliding contact surface. Whether or not insulating particles are present in the gaps between the particles of the soft magnetic powder on the sliding surface of the compressed powder body thus produced can be confirmed, for example, by surface observation using electron probe microanalysis (EPMA) or surface observation using SEM-EDX.
[0072] When the amount of insulating particles contained in the insulating lubricating coating formed on the inner peripheral surface of the cavity of the mold becomes large, the surplus insulating particles that cannot be pushed into the spaces between the particles of the soft magnetic powder on the sliding surface of the compact adhere to the surface of the sliding surface of the compact, and the sliding surface of the compact may be further coated with the surplus insulating particles. For example, the surface of the sliding surface of the compact may be coated with molybdenum disulfide particles, insulating ceramic particles, or a combination of these. This coated region is preferably within the range of the region having a resistivity of 5 Ω·cm or more as described above.
[0073] When insulating ceramic particles are contained in the insulating lubricating coating formed on the inner peripheral surface of the cavity of the mold, and the insulating ceramic particles are present between the particles of the soft magnetic powder on the sliding surface of the green compact, the resistivity of the surface layer of the green compact may be high and the resistivity of the inside of the green compact may be low compared to the surface layer due to the insulating properties of the insulating ceramic particles themselves. This high resistivity of the surface layer can effectively suppress an increase in eddy current loss We in a state in which induced currents flow intensively on the surface of the green compact in a high frequency environment.
[0074] In regions where an insulating lubricating coating is not formed on the inner circumferential surface of the mold cavity, frictional resistance is likely to cause plastic flow on the sliding surface of the green compact when it is pushed out of the mold cavity. This plastic flow occurs most strongly on the outermost surface of the sliding surface of the green compact, and the effects of frictional resistance can generally extend to a region up to a depth of about 20 μm from the outermost surface. In regions where this plastic flow occurs, the insulation between the particles of the soft magnetic powder on the sliding surface of the green compact decreases, and a region having a resistivity of 1 Ω cm or less as described above can be formed. In the region where the insulating lubricating coating is formed on the inner circumferential surface of the mold cavity, when the green compact is extruded from the mold cavity, the insulating particles are interposed between the particles of the soft magnetic powder on the sliding surface of the green compact to support the soft magnetic powder particles, thereby suppressing the occurrence of plastic flow. In order to obtain this effect, it is preferable that the insulating particles penetrate and are dispersed in a region within 1 mm from the outermost surface of the sliding surface of the green compact, preferably in a region with a depth of 1 μm to 100 μm. In this region where the occurrence of plastic flow is suppressed, the insulation between the particles of the soft magnetic powder is maintained on the sliding surface of the green compact, so that the above-mentioned region having a resistivity of 5 Ω·cm or more can be formed. Even if the region having a resistivity of 5 Ω·cm or more is formed partially rather than entirely on the sliding surface of the green compact, the insulation can be maintained and the increase in iron loss can be suppressed. Furthermore, the depth of the surface region where induced current concentrates in a powder magnetic core in a high frequency environment depends on the frequency, but at least at frequencies of about 1 kHz to 50 kHz, the resistivity is increased by the insulating particles in the region deep from the outermost surface of the sliding contact surface of the above-mentioned powder compact, which is sufficient to deal with the problem.
[0075] When insulating particles are present between the particles of the soft magnetic powder in the surface layer of the sliding surface of the compact, and the insulating particles surround and constrain each particle of the soft magnetic powder, resulting in a discontinuous state between adjacent particles of the soft magnetic powder, the occurrence of electrical conduction between the particles of the soft magnetic powder can be further suppressed. In other words, in the region of the sliding surface of the compact having a resistivity of 5 Ω·cm or more as described above, the higher the discontinuity, the higher the resistivity, which is a preferable state. In addition, this discontinuous state further suppresses the occurrence of plastic flow, since the insulating particles firmly constrain each particle of the soft magnetic powder.
[0076] In the insulating lubricating coating, the ratio of the insulating particles to the total amount of the lubricating oil and the insulating particles is preferably 20 to 90 mass %, more preferably 30 to 80 mass %, and even more preferably 40 to 80 mass %.
[0077] When the insulating lubricating coating contains molybdenum disulfide particles, the insulating lubricating coating formed on the inner circumferential surface of the mold cavity preferably contains molybdenum disulfide particles in a proportion of 30 to 80 mass%, more preferably 40 to 80 mass%, and may be 50 to 70 mass%, relative to the total amount of lubricating oil and insulating particles. When the proportion of the molybdenum disulfide particles is 30% by mass or more, the molybdenum disulfide particles impart lubricity between the inner circumferential surface of the mold cavity and the sliding surface of the powder compact, reducing frictional resistance and further suppressing the occurrence of plastic flow at the sliding surface. Also, the presence of molybdenum disulfide particles between the particles of the soft magnetic powder at the sliding surface of the powder compact can further suppress the occurrence of plastic flow at the sliding surface. When the ratio of the molybdenum disulfide particles is 80 mass% or less, a sufficient amount of lubricating oil can promote the formation of a coating and fix the insulating particles to the inner circumferential surface of the mold cavity. Also, a sufficient amount of lubricating oil can be secured as a carrier to introduce the insulating particles between the particles of the soft magnetic powder on the sliding surface of the compact. Also, a sufficient amount of lubricating oil can ensure lubricity between the inner circumferential surface of the mold cavity and the sliding surface of the compact, particularly lubricity against dynamic friction, and can further prevent plastic flow on the sliding surface of the compact.
[0078] When the insulating lubricating coating contains insulating ceramic particles, the insulating lubricating coating formed on the inner circumferential surface of the mold cavity preferably contains 1 to 10 mass % of insulating ceramic particles relative to the total amount of lubricating oil and insulating particles. By making the proportion of the insulating ceramic particles 1 mass % or more, the insulating ceramic particles can be more effectively interposed between the particles of the soft magnetic powder, and the resistivity of the sliding surface of the powder magnetic core can be further increased. By making the proportion of the insulating ceramic particles 10 mass % or less, the proportion of hard insulating ceramic particles is reduced, and the amount of insulating ceramic particles present between the inner peripheral surface of the mold cavity and the sliding surface of the powder compact is made appropriate, so that the inner peripheral surface of the mold cavity or the sliding surface of the powder compact can be prevented from being worn away by excess insulating ceramic particles. Also, when the soft magnetic powder has an insulating coating, the insulating coating of the soft magnetic powder can be prevented from being destroyed by excess insulating ceramic particles. When an insulating lubricating coating contains molybdenum disulfide particles and insulating ceramic particles, it is preferable that the blending ratios of each satisfy the above-mentioned ranges.
[0079] The insulating lubricating coating may contain optional additives such as viscosity modifiers, dispersants, and high molecular weight polymers.
[0080] The insulating lubricating coating can be formed by applying a lubricating composition to the inner peripheral surface of the cavity of the molding die. The lubricating composition may include a lubricating oil and insulating particles. The insulating particles may include at least one selected from the group consisting of molybdenum disulfide particles and insulating ceramic particles, and preferably include at least molybdenum disulfide particles. The lubricating composition preferably includes a lubricating oil and molybdenum disulfide particles, or a lubricating oil, molybdenum disulfide particles, and insulating ceramic particles.
[0081] The lubricating oil is added to the lubricating composition as a dispersion medium for the insulating particles. The lubricating composition is preferably in the form of a semi-solid or highly viscous liquid capable of forming a film. A flowable insulating lubricating coating can be formed by applying the lubricating composition to the inner circumferential surface of the cavity of the mold. The insulating lubricating coating formed on the inner circumferential surface of the cavity of the mold can reduce friction between the inner circumferential surface of the mold cavity and the sliding surface of the powder compact when the powder compact is removed from the mold due to its lubricity.
[0082] When the lubricating composition contains molybdenum disulfide particles, the molybdenum disulfide particles function as a solid lubricant and are particularly effective in reducing static friction.When the lubricating composition contains molybdenum disulfide particles and a lubricating oil, the lubricating oil is preferably a low-viscosity liquid lubricating oil, since it is preferable that the lubricating oil functions more effectively in reducing dynamic friction.By combining the molybdenum disulfide particles and the low-viscosity liquid lubricating oil, the frictional resistance during the extrusion of the powder compact from the mold can be further reduced. Liquid lubricating oil is easily absorbed by capillary force into the gaps between the particles of the soft magnetic powder on the sliding surface of the compact, and can also function as a carrier that supplies insulating particles to the gaps between the particles of the soft magnetic powder on the sliding surface of the compact. Lubricating oils are broadly divided into two types: mineral oils made by refining crude oil, and synthetic oils produced by chemical processes. Either type is acceptable, but mineral oil-based lubricating oils are preferred because they are inexpensive and widely used.
[0083] The viscosity of the lubricating oil is 1000mm at 25°C. 2 / s~100000mm 2 / s is preferred. The viscosity of the lubricating oil is 100,000 mm 2 By setting the viscosity at 0.05 to 1.0 MPa or less, the powder can have a flowability suitable for use as a carrier when insulating particles are supplied to gaps between particles of the soft magnetic powder on the sliding contact surface of the green compact. Also, the coating property onto the inner peripheral surface of the cavity of the molding die can be improved. The viscosity of the lubricating oil is 1000mm 2 By ensuring that the composition has a molecular weight of at least 1000, dripping and the like can be prevented when the composition is applied to the inner peripheral surface of the cavity of a casting mold, and film formability can be further improved. The viscosity of the lubricating oil can be adjusted by blending a viscosity modifier such as a thickener. A viscosity modifier may be added to the lubricating oil as appropriate so that the lubricating oil has the above-mentioned kinetic viscosity.
[0084] The lubricating composition preferably contains lubricating oil and insulating particles in a mixture equivalent to the composition of the insulating lubricating coating applied to the inner circumferential surface of the mold cavity. The preferred composition of the insulating lubricating coating is as described above. For example, the lubricating composition preferably contains 30 to 80 mass% of molybdenum disulfide particles relative to the total amount of lubricating oil and insulating particles, and 20 to 70 mass% of insulating particles relative to the total amount of lubricating oil and insulating particles.
[0085] The lubricating composition may contain optional additives such as viscosity modifiers such as thickeners, dispersants, high molecular weight polymers, etc. Such additives may be appropriately selected from those commonly used. When a viscosity modifier is added to the lubricating composition, the blending ratio may be determined by replacing a part of the blending amount of the lubricating oil with a thickener. A dispersant may be added to uniformly disperse the insulating particles in the lubricating oil. When a dispersant is added to the lubricating composition, the dispersant may be added in a ratio of 1 to 10 parts by mass per 100 parts by mass of the insulating particles. When other additives such as a polymer are added to the lubricating composition, the additives may be added in a ratio of 1 to 10 parts by mass per 100 parts by mass of the insulating particles. A method for preparing the lubricating composition may include, for example, adding additives to a lubricating oil and mixing them uniformly, and adding insulating particles such as molybdenum disulfide particles and insulating ceramic particles thereto and mixing and dispersing them uniformly. The lubricating composition may be applied to the inner surface of the mold cavity in a conventional manner, for example, by applying the composition with a brush or the like, by applying masking tape to the non-coated area and then applying the composition with a brush or the like, or by pouring the lubricating composition into the mold cavity and removing the excess lubricating composition.
[0086] The insulating lubricating coating is preferably formed on the inner circumferential surface of the mold cavity in a thickness of 0.1 μm to 20 μm. The thickness of the insulating lubricating coating is preferably 0.1 μm or more, more preferably 1 μm or more, and even more preferably 10 μm or more. This allows a sufficient amount of lubricating oil and insulating particles to be applied between the inner peripheral surface of the die cavity and the sliding surface of the powder compact. In addition, the frictional resistance between the die cavity and the powder compact can be reduced, and the occurrence of plastic flow on the sliding surface of the powder compact can be further suppressed. The thickness of the insulating lubricating coating is preferably 50 μm or less, more preferably 30 μm or less, and even more preferably 20 μm or less. This can prevent a decrease in dimensional accuracy due to the thickness of the insulating lubricating coating when the raw material powder is filled into the die cavity and compressed. In addition, by making the thickness of the insulating lubricating coating 20 μm or less, it is possible to more reliably ensure that the region on the inner circumferential surface of the die cavity where the insulating lubricating coating is not formed and the sliding surface of the green compact come into contact with each other, and the sliding surface of the green compact undergoes a certain degree of plastic flow in this portion, thereby forming a region with low resistivity. In addition, it is possible to prevent excess components of the insulating lubricating coating from flowing out from the region on the inner circumferential surface of the die cavity where the insulating lubricating coating is formed to the region on which the insulating lubricating coating is not formed, and it is possible to more reliably ensure the region on which the insulating lubricating coating is not formed.
[0087] Next, a method will be described in which raw material powder containing soft magnetic powder is filled into a cavity of a molding die, the raw material powder is compressed to form a green compact, and the green compact is extruded from the cavity. The filling method, compression method and extrusion method are not particularly limited and may be carried out according to a conventional method.
[0088] The raw material powder is preferably compressed so that the density ratio of the green compact is 91% or more. The molding pressure can be appropriately adjusted to obtain the above density ratio, and may be, for example, 600 to 1500 MPa. The molding pressure is preferably applied in one axial direction, that is, the extrusion direction. The molding may be performed at room temperature, but may also be performed under heating. The extrusion method can be, for example, by moving a punch member at one end of the mold toward the other end, so that the powder compact is extruded toward the other end.
[0089] The raw material powder may include soft magnetic powder. Details of the soft magnetic powder are as described above. The raw material powder may further include additives such as a binder such as a resin, a molding lubricant, and insulating ceramic particles. By including a binder such as resin in the raw powder, the filling property of the soft magnetic powder can be improved, and the compression moldability can be improved. The binder is preferably 2 mass% or less of the total amount of the raw powder. Examples of the binder include polyvinylpyrrolidone.
[0090] As described above, an insulating lubricating coating is formed on the inner peripheral surface of the die cavity of the compact, and the insulating lubricating coating contains lubricating oil and insulating particles, which reduces frictional resistance when the green compact is pushed out of the die cavity, and can suppress the occurrence of plastic flow at the sliding surface of the green compact. Therefore, it is not necessary to add a lubricant to the raw material powder. If the raw material powder does not contain a lubricant or contains a small amount of lubricant, it is possible to prevent a decrease in the flowability of the raw material powder, improve the filling ability of the raw material powder into the die cavity, and increase the space factor of the soft magnetic powder in the obtained green compact. When a lubricant is added to the raw material powder, the lubricant is preferably 0.1 to 2.0 mass % of the total amount of the raw material powder, and more preferably 0.2 to 1.0 mass %. Examples of the lubricant include zinc stearate. This can increase the lubricity of the entire outer surface of the green compact. Molybdenum disulfide particles may be added to the raw material powder as a solid lubricant.
[0091] Insulating particles may be added to the raw powder, but they do not have to be added. For example, insulating ceramic particles can be added to the raw powder because they have low magnetic permeability. This makes it possible to obtain a green compact in which insulating ceramic particles are dispersed in the pores, and to provide a green compact with a constant magnetic permeability and in which magnetic gaps are dispersed. When the insulating ceramic particles are added to the raw powder, the insulating ceramic particles are preferably mixed in an amount of 1.5 volume % or less based on the total raw powder. This prevents excessive insulating ceramic particles from entering the pores of the green compact, and allows the insulating particles to enter the gaps between the particles of the soft magnetic powder on the sliding surface of the green compact from the insulating lubricating coating formed on the inner circumferential surface of the die cavity during compression molding. In addition, the flowability and moldability of the raw powder are prevented from decreasing, and the compression moldability can be further improved.
[0092] As the insulating ceramic particles, lipophilic insulating ceramic particles can be used. This allows the insulating ceramic particles to be more uniformly dispersed in the lubricating oil when preparing the lubricating composition, and allows the insulating ceramic particles to be more uniformly distributed in the insulating lubricating coating formed on the inner circumferential surface of the mold cavity. As the lipophilic insulating ceramic particles, insulating ceramic particles whose surface has been modified with a coupling agent can be preferably used. Examples of the coupling agent include silane-based coupling agents, aluminate-based coupling agents, titanate-based coupling agents, etc. These coupling agents may be used alone or in combination of two or more. When a silane coupling agent is used, a surface treatment layer is formed on the surface of the insulating ceramic particles with a compound containing Si. When an aluminate coupling agent is used, a surface treatment layer is formed on the surface of the insulating ceramic particles with a compound containing Al. When a titanate coupling agent is used, a surface treatment layer is formed on the surface of the insulating ceramic particles with a compound containing Ti. Such an organic surface treatment layer is also an insulating coating. The surface modification of the insulating ceramic particles with a coupling agent may be carried out according to a conventional method. For example, surface modification with a silane coupling agent may be carried out by a direct treatment method (dry or wet), an integral blend method, a primer type treatment method, etc. In addition, surface-modified insulating ceramic particles may be appropriately selected from commercially available powder products.
[0093] When using a soft magnetic coating having an insulating coating as the soft magnetic powder, particularly when using a soft magnetic coating having an inorganic phosphate coating, an organic silicone coating, or the like, by using insulating ceramic particles whose surface has been modified with a coupling agent, the affinity between the insulating powder particles and the insulating ceramic particles during compression molding can be improved, and the compression moldability can be further improved. In particular, when a soft magnetic powder having a silicone insulating coating is combined with insulating ceramic particles whose surface has been modified with a silane coupling agent, the affinity between them is high, so that the insulating ceramic particles are adsorbed or coated on the particle surface of the soft magnetic powder during compression molding, thereby further improving the insulation of the particles of the soft magnetic powder. In addition, by using insulating ceramic particles, it is possible to prevent direct contact between the soft magnetic powder particles and the inner surface of the mold hole, and prevent the destruction of the soft magnetic powder particles and the wear of the inner surface of the mold hole.
[0094] By adsorbing insulating ceramic particles to the particle surfaces of the soft magnetic powder, the insulating state at the surface layer of the sliding surface of the compact can be maintained or improved, and an increase in eddy current loss in the compacted powder core due to deterioration of the insulation at the sliding surface of the compacted powder can be suppressed. When the lubricating composition contains lipophilic insulating ceramic particles, the molybdenum disulfide particles have a lower affinity for the soft magnetic powder than the insulating ceramic particles, and therefore tend to concentrate in the gaps between the particles of the soft magnetic powder. In the gaps between the particles of the soft magnetic powder, the molybdenum disulfide particles cleave to relieve stress while also providing a lubricating effect.
[0095] The powder compact after compression molding may be used as it is as a powder magnetic core, but may be subjected to a heat treatment as necessary. For example, in order to improve the effect of hysteresis loss when used as a powder magnetic core, an annealing heat treatment may be performed to release the compression strain accumulated in the powder compact. In addition, when the powder compact contains a thermosetting resin as a binder, a heat treatment may be performed in which the powder compact is heated to the hardening temperature of the thermosetting resin. Alternatively, when the powder compact contains a thermoplastic resin as a binder, a heat treatment may be performed in which the powder compact is heated to the softening temperature of the thermoplastic resin. These heat treatments may be performed according to a conventional method. In these heat treatments, the lubricating oil and insulating particles applied to the sliding surface of the powder compact do not diffuse into the powder compact or have little effect thereon in the temperature range of heat treatments generally performed on the powder compact, so they have little effect on the magnetic properties of the resulting powder core. However, the lubricating oil may decompose and disappear when the powder compact is subjected to heat treatment.
[0096] When the powder compact after compression molding is used as a powder core without being heat-treated, the lubricating oil on the surface of the powder compact remains. In order to remove the lubricating oil on the surface of the powder compact, for example, the powder compact may be washed with a solvent.
[0097] In a method for producing a green compact for a dust core, it is preferable to form an insulating lubricating coating in a predetermined region of the inner circumferential surface of the die cavity of a molding die to obtain a green compact having regions with different resistivities on the sliding surfaces, but the resistivities of both end faces (punch surfaces) intersecting the extrusion direction are not particularly limited. Therefore, an insulating lubricating coating may be formed on the surface of the punch member that comes into contact with the green compact, but it is not necessary to form an insulating lubricating coating thereon.
[0098] According to one embodiment, a molding die for producing a powder magnetic core is provided, the molding die having a die hole for compressing a raw material powder to form a powder compact, and an insulating lubricating coating formed on the inner peripheral surface of the die hole in a region of 20% to 80% of the entire inner peripheral length along a circumferential direction with the extrusion direction of the die hole as an axis. The insulating lubricating coating preferably contains a lubricating oil and insulating particles. The insulating particles preferably contain at least one type selected from the group consisting of molybdenum disulfide particles and insulating ceramic particles, and more preferably contain at least molybdenum disulfide particles.
[0099] According to another embodiment, there is provided a molding apparatus for producing powder magnetic cores, comprising the above-mentioned molding die for producing powder magnetic cores, and upper and lower punch members for compressing raw material powder within the die cavity. According to yet another embodiment, there is provided a lubricating composition for a molding die for producing a powder magnetic core, the lubricating composition comprising a lubricating oil and insulating particles, the insulating particles preferably comprising at least one selected from the group consisting of molybdenum disulfide particles and insulating ceramic particles, and more preferably comprising at least molybdenum disulfide particles. EXAMPLES
[0100] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0101] <Example 1> (Preparation of Lubricating Composition) Titanium oxide powder (particle diameter: 100 nm) was prepared as insulating ceramic particles. The insulating ceramic particles had an organic coating formed by surface modification with a silane coupling agent (n-butyltrimethoxysilane). In addition, a thickener (SOLGAM SH 210 manufactured by Seiwa Kasei Co., Ltd.) was used as a lubricant to increase the kinetic viscosity at 25°C to 10,000 mm. 2 A mineral oil (Nuto H32 manufactured by Exxon Mobil Corp.) adjusted to 0.1% by mass / s was prepared. The lubricating oil, insulating ceramic particles, and molybdenum disulfide particles (particle diameter: 0.5 μm) were mixed together and uniformly dispersed so that the ratios of the insulating ceramic particles and the molybdenum disulfide particles to the total amount were 5 mass% and 50 mass%, respectively.
[0102] (Forming of powder compacts) A lower punch was fitted into a mold having a cylindrical hole with an inner diameter of 20 mm to form a molding cavity, and the lubricating composition prepared as described above was applied to the inner surface of the mold hole and dried to form a lubricating coating with a thickness of approximately 20 μm on the inner surface of the mold hole. In the mold cavity for Sample No. 1, no lubricating composition was applied to the inner circumferential surface of the mold cavity. For the mold cavities for sample numbers 2 to 4, the lubricating composition was applied to the inner surface of the mold cavity along the circumferential direction to widths of 2%, 10%, and 25% of the total inner circumference, respectively, and no lubricating composition was applied to any other areas. For the mold cavity for sample number 5, the entire inner circumference of the mold cavity was coated with the lubricating composition. In the die cavities for sample numbers 2 to 5, the lubricating composition was applied over the entire length of each die cavity in the extrusion direction. As the raw material powder, an iron-based soft magnetic powder with an insulating coating on the surface (Somaloy110i (5P) manufactured by Höganäs AB, main particle size distribution: 45 to 75 μm) was prepared, and 60 g of the powder was placed in each of the die holes for the above-mentioned sample numbers 1 to 5. The raw material powder was compression molded at a molding pressure of 1200 MPa using an upper punch, and extruded to obtain cylindrical green compacts of sample numbers 1 to 5. The density of the green compacts was measured by the Archimedes method, and the density ratio of the green compacts was calculated. The results are shown in Table 1.
[0103] (Method of evaluating surface resistivity) The surface resistivity of the obtained cylindrical green compact was measured by the four-point probe method using a resistivity meter "Loresta GP" (PSP probe) manufactured by Nitto Seiko Analytech Co., Ltd. The terminal row of the PSP probe was pressed against the sliding surface so that it was parallel to the sliding direction. The resistivity was measured at 50 equally spaced points around the circumference of the sliding surface, and the area of the surface resistivity was calculated as follows: Area with surface resistivity of 5 Ω cm or more: ((measurement points with surface resistivity of 5 Ω cm or more) / (total measurement points)) x 100 (%). Area with surface resistivity of 1 Ωcm or less: ((measurement points with surface resistivity of 1 Ωcm or less) / (total measurement points)) x 100(%). For the measurement points where the surface resistivity was 5 Ωcm or more, the average value was calculated to obtain the surface resistivity of the high resistivity area. Similarly, for the measurement points where the surface resistivity was 1 Ωcm or less, the average value was calculated to obtain the surface resistivity of the low resistivity area. The results are shown in Table 1.
[0104] (Observation of the side surface of the compact) The side of the obtained green compact was observed using an EPMA device, and the area ratio (%) of molybdenum disulfide particles in the component map of the side was examined. The area ratio was measured by analyzing the image taken at a magnification of 100 times using image analysis software (Quick grain standard) (threshold: RGB: 160). Furthermore, in order to evaluate the state of the soft magnetic powder particles on the side of the green compact, the presence or absence of plastic flow of the soft magnetic powder particles was examined in the SEM image of the side. The presence or absence of plastic flow was determined by the presence or absence of sliding marks in the SEM image, and also by the presence or absence of flow of Fe elements in the component map by EPMA, that is, whether or not Fe elements were detected between the particles of the soft magnetic powder. Even if no clear sliding marks were confirmed, if Fe elements were detected between the particles of the soft magnetic powder, plastic flow of the soft magnetic powder occurs. It is considered that when plastic flow occurs, bonding occurs due to conduction between the particles of the soft magnetic powder. The judgment results of the presence or absence of plastic flow of the soft magnetic powder examined in this way are shown in Table 1.
[0105] (Method of evaluating iron loss) A reactor was assembled so that the punch surface of the obtained cylindrical green compact became the magnetic pole surface, and an excitation coil and a search coil were wound around the legs. The iron loss was measured at 5 kHz and 20 kHz at a magnetic flux density of 20 mT using a BH analyzer "SY-8258" manufactured by Iwasaki Electric Co., Ltd. The results are shown in Table 1.
[0106] (Method of evaluating dimensional accuracy) The length of the cross section perpendicular to the extrusion direction, i.e., the diameter, of the obtained cylindrical green compact was measured using a micrometer. The dimensional accuracy was evaluated from the maximum and minimum values of the lengths of the five green compacts. Five green compacts were produced using the same mold, and the dimensions of the five green compacts were measured. If the difference between the maximum and minimum dimensions of the five green compacts was small, the dimensional accuracy was deemed good, and the dimensional accuracy was evaluated. The evaluation results are shown in Table 1. In Table 1, A indicates good, and B indicates poor.
[0107] [Table 1]
[0108] As shown in Table 1, dust cores in which a high resistivity region and a low resistivity ratio were distinguished were obtained in sample numbers 2 to 4. It was also found that the high resistivity ratio determined by the measurement of surface resistivity almost corresponds to the region of the lubricating composition applied to the inner circumferential surface of the die cavity. Since no plastic flow was observed in the high resistivity portion, it was found that the occurrence of plastic flow was suppressed in the region where the lubricating composition was applied, and a high resistivity region was formed. It was also found that plastic flow occurred in the region where the lubricating composition was not applied, and a low resistivity region was formed. In sample No. 4, in which the high resistivity ratio was 26%, a dust core with low iron loss and high dimensional accuracy was obtained. In sample No. 1, the lubricating composition was not applied to the inner circumferential surface of the die cavity, and plastic flow occurred over the entire circumference of the dust core, decreasing the surface resistivity. In sample Nos. 2 and 3, the ratio of the area in which the lubricating composition was applied to the inner circumferential surface of the die cavity was small, and the ratio of plastic flow that occurred in the dust core increased and the high resistivity ratio decreased. As a result, the iron loss increased in sample Nos. 1 to 3. In sample No. 5, the lubricating composition was applied to the entire inner circumferential surface of the die cavity, and the occurrence of plastic flow was suppressed over the entire circumference of the dust core, and the surface resistivity was high over the entire circumference of the dust core. However, the dimensional accuracy of sample No. 5 deteriorated. For sample numbers 2 to 5, the area ratio of molybdenum disulfide in the high resistivity portion is high, and it is found that the lubricating composition applied to the inner peripheral surface of the die cavity is attached to the outer peripheral surface of the powder core. In addition, for sample numbers 1 to 4, molybdenum disulfide was hardly observed in the low resistivity portion. From this, it is found that it is possible to specify the high resistivity ratio and the low resistivity ratio by confirming the ratio between the region where insulating particles such as molybdenum disulfide are attached to the outer peripheral surface of the powder core at a certain ratio and the region where these insulating particles are hardly observed. It is also found that a method of applying insulating particles to the outer peripheral surface of the powder core to form a high resistivity portion is effective.
[0109] (Evaluation of eddy current loss and hysteresis loss) Coils were wound with the same number of turns around the powder cores of sample numbers 2 and 4 as cores, and the eddy current loss and hysteresis loss were measured under the same conditions of a frequency of 50 kHz and a magnetic flux density of 0.01 T. The results are shown in Table 2. Compared to the powder core of sample number 2, the eddy current loss in the powder core of sample number 4 was clearly less. This is thought to be because the proportion of high resistivity in sample number 4 is large, and therefore the generation of eddy currents is suppressed on the outer peripheral surface of the powder core.
[0110] [Table 2] [Industrial Applicability]
[0111] The powder magnetic core of the present invention can be applied to transformers, reactors, thyristor valves, noise filters, choke coils, etc., and can also be applied to motor cores, rotors and yokes of motors for general home appliances and industrial equipment, solenoid cores (fixed cores) for solenoid valves incorporated in electronically controlled fuel injection devices for diesel engines and gasoline engines, etc. It is particularly effective when applied to reactors used in the high frequency range.
Claims
1. a green compact obtained by compression molding of soft magnetic powder, wherein a sliding surface of the green compact has an area having a resistivity of 5 Ω cm or more in a range of 20 area % to 30 area % of the entire sliding surface, and an area having a resistivity of 1 Ω cm or less in a range of 20 area % to 80 area % of the entire sliding surface, The region having a resistivity of 5 Ω cm or more is formed in an area having a width of 20% to 30% in the circumferential direction, across the axial direction, The region having a resistivity of 1 Ω cm or less is formed in an area having a width of 20% to 80% in the circumferential direction, across the axial direction.
2. 2. The powder magnetic core according to claim 1, wherein the region having a resistivity of 5 Ω·cm or more has a surface layer portion having a structure in which insulating particles are present between particles of the soft magnetic powder.
3. 2. The powder magnetic core according to claim 1, wherein the region having a resistivity of 5 Ω·cm or more has an area ratio of insulating particles of 30% or more in a component map obtained by electron probe microanalysis.
4. The powder magnetic core according to claim 2 or 3, wherein the insulating particles include at least one type selected from the group consisting of molybdenum disulfide particles and insulating ceramic particles.
5. The powder magnetic core according to claim 1 , wherein the soft magnetic powder has an insulating coating covering a surface of the soft magnetic powder.
6. forming an insulating lubricating coating on the inner peripheral surface of the mold cavity of the molding die; Filling a raw material powder containing a soft magnetic powder into a mold cavity of the molding die; compressing the raw material powder to form a green compact; and ejecting the powder compact from the die cavity; a molding die hole having an inner circumferential surface and an insulating lubricating coating formed thereon, the insulating lubricating coating being formed along a circumferential direction whose axis is the extrusion direction of the molding die, in an area having a width of 20% to 40% of the entire inner circumferential length, across the extrusion direction.
7. The method for producing a magnetic core green compact according to claim 6 , wherein the insulating lubricant coating contains a lubricant oil and insulating particles.
8. The method for producing a green compact for a magnetic core according to claim 7 , wherein the insulating particles include at least one type selected from the group consisting of molybdenum disulfide particles and insulating ceramic particles.
9. 9. The method for producing a powder compact for a magnetic core according to claim 6, wherein the insulating lubricant coating is formed over an area that is 50% or more and 100% or less of the entire length of the pressing die in the extrusion direction.
10. The method for producing a magnetic core green compact according to any one of claims 6 to 9, wherein the insulating lubricant coating has a thickness of 1 µm to 20 µm.
Citation Information
Patent Citations
Molding method of green compact
JP2012248619A
Green compact, core for reactor, reactor, converter, and electric power conversion system
JP2013131676A
Powder magnetic core, method for manufacturing powder compact for magnetic core, pressing die and mold device for manufacturing powder magnetic core, and lubricant composition for pressing die for manufacturing powder magnetic core
WO2015046282A1